Nostalgia de la encomienda. Releer el Tratado del descubrimiento, de Juan Suárez de Peralta (1589) - González González, Enrique (El Colegio de México, A.C., 2009)
The work Tratado del descubrimiento de las Yndias y su conquista, written  by the New Spain Creole Juan Suárez de Peralta around 1589, has traditionally been read as just another Conquest chronicle, scarcely interesting in its first chapters, but fully vivid in its “second” part, where the author  tells of the so-called conspiracy of Martín Cortés,  Second Marquis of the Valley of Oaxaca. This paper, however, suggests that the Tratado, in keeping with its title, must be read as a treatise in which Suárez de Peralta pleads for the legitimacy of the encomienda and offers an account of the fateful —as he sees them— consequences  brought about by the Crown's rulings to suppress it. Therefore, the Tratado must be considered within the great debates of the time on how conquered peoples, conquerors and their descendants  should be treated. Although not a professional lawyer, Suárez de Peralta turns out to be a resourceful and convincing writer. Far from offering a linear account  of a series of events, he takes advantage of ambiguity in order  to argue, from different  viewpoints,  on several issues. Sensing that he defends a lost cause, his allegation oozes irony, disillusion, and nostalgia.